Towards the Eradication of Helicobacter pylori Infection (IntechOpen, 2024)
"Towards the Eradication of Helicobacter pylori Infection - Rapid Diagnosis and Precision Treatment" book is a comprehensive guide to combating one of the most persistent challenges in global public health. In this volume, experts from various disciplines have joined forces to present the latest research, clinical insights, and practical applications for diagnosing and treating H. pylori infection. The chapters present in this volume cover diagnostic modalities in detecting H. pylori infection, from rapid noninvasive techniques for detecting antibiotic resistance to the utility of linked color imaging in endoscopic diagnosis. The book also presents innovative treatment strategies, including the role of cytokines in inflammation, the impact of antibiotic resistance patterns, and the potential of immunotherapeutic approaches. Healthcare professionals, researchers, and students should benefit from this volume in developing the knowledge and tools necessary to combat and eradicate H. pylori infection effectively.